Dinâmica da política monetária e operações compromissadas: uma análise do caso brasileiro - Moraes, Aline Rodrigues de (2020)
The aim of this paper is to analyze the determinants of repurchase agreements and the management of Brazilian monetary policy, between 2011 and 2018. ARDL Bounds Testing Approach estimations indicated that: (i) the selected variables cointegrate in the long run and, therefore, they are relevant to explain the expansionary movement of repurchase agreements; (ii) international reserves showed a behavior directly proportional to the balance of repurchase agreements, while the primary result showed an inversely proportional behavior; (iii) there is a low speed of adjustment to short term shocks and (iv) currency swaps and interest payments on repo are not statistically significant, although they are important in the joint significance of the variables, in the long run.